2021
DOI: 10.5650/jos.ess21032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Cholesterol-Lowering Effect of Scallop Oil Prepared from the Internal Organs of the Japanese Giant Scallop (<i>Patinopecten yessoensis</i>), Fish Oil, and Krill Oil in Obese Type II Diabetic KK-<i>A</i> <sup> <i>y</i> </sup> Mice

Abstract: IntroductionThe increase in the incidence of lifestyle-related diseases, including obesity, dyslipidemia, and cardiovascular diseases CVD , has become a social problem in developed countries. In particular, CVD, which causes arteriosclerosis, is one of the leading causes of morbidity and mortality worldwide 1 . Therefore, the prevention or amelioration of dyslipidemia, such as hypertriglyceridemia and hypercholesterolemia, would reduce the risk of CVD 2 . Dietary n-3 polyunsaturated fatty acids PUFA , includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Our previous study demonstrated that SCO intake decreased the serum and liver cholesterol content compared with n-3 PUFAcontaining oils, including tuna oil, menhaden oil, and krill oil (28,29). However, it is unclear whether the FA composition or PL of SCO is responsible for this cholesterol-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study demonstrated that SCO intake decreased the serum and liver cholesterol content compared with n-3 PUFAcontaining oils, including tuna oil, menhaden oil, and krill oil (28,29). However, it is unclear whether the FA composition or PL of SCO is responsible for this cholesterol-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…The PL contents of the experimental oils were measured using a phosphorus assay ( 34 ). The PL class compositions of SOY-PL and SCO-PL were analyzed by thin-layer chromatography using authentic PL standards, ceramide aminoethyl phosphate (CAEP), phosphatidic acid (PtdOH), PtdCho, phosphatidylethanolamine (PtdEtn), and phosphatidylinositol (PtdIns), according to our previous report ( 29 ). The glycerophospholipid (GPL) subclass composition of the experimental oils was analyzed based on the methods described by Dawson ( 35 ), with some modifications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations